Factors Affecting Earnings Persistence in Pharmaceutical Companies on the Indonesia Stock Exchange - Jihan Nur Aprian; Natali Yustisia (Indonesian Development of Economics and Administration Journal, 2022)
This study aims to analyze the effect of debt levels, sales volatility and company size on profit persistence in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The sampling technique used was purposive sampling and obtained 60 samples from 10 companies. The analytical method used was panel data regression analysis with Eviews 12. The results showed that the level of debt and sales volatility partially had a negative effect on earnings persistence while firm size had no effect on earnings persistence. Meanwhile, the Adjusted R-Square is 42.57%. This explains that there are other factors outside the variables that have been studied at 57.43% which affect earnings persistence.